2020
DOI: 10.1111/1748-5967.12465
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial but not fungal challenge up‐regulates the transcription of Coleoptericin genes in Tenebrio molitor

Abstract: Antimicrobial peptides (AMPs) are effector candidates that elicit humoral immunity in invertebrates. AMPs facilitate bacterial clearance by either physically disrupting the microbial membranes or the intracellular targets. In the Coleopteran pest, Tenebrio molitor, transcriptional regulation of AMPs has been studied in the context of innate immune signaling cascades and antimicrobial immunity. Here, we report the transcriptional response of three AMP genes, Coleoptericin A, B, and C (TmCole A, B and C) in T. m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The viability of E. coli -infected TmSpz-like knockdown T. molitor larvae may have decreased due to the downregulation of the AMP-encoding genes. These AMPs are reported to exert growth-inhibitory activity against E. coli [ 35 , 36 , 37 , 38 , 39 , 40 ]. Tm Tenecin3, an antifungal peptide, and Tm Thaumatin-like proteins are majorly induced in plant systems due to stress and other pathogenic insults [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The viability of E. coli -infected TmSpz-like knockdown T. molitor larvae may have decreased due to the downregulation of the AMP-encoding genes. These AMPs are reported to exert growth-inhibitory activity against E. coli [ 35 , 36 , 37 , 38 , 39 , 40 ]. Tm Tenecin3, an antifungal peptide, and Tm Thaumatin-like proteins are majorly induced in plant systems due to stress and other pathogenic insults [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…4 and Tables S2 and S3), but this overexpression is profound in the recently established population of O. rhinoceros in the Solomon Islands (log 2 FC, >10). Previous studies showed upregulation of this protein in mealworm beetle ( Tenebrio molitor ) parasitized by Scleroderma guani ( 53 ) and after bacterial challenge ( 54 ). It has been shown that the expression and production of this AMP is dependent on the immune deficiency (Imd) pathway in the cereal weevil Sitophilus ( 55 ).…”
Section: Resultsmentioning
confidence: 99%
“…Expression patterns of 14 AMP genes including TmTenecin1, 2, 3 , and 4 ( TmTene1 , − 2 , − 3 , and − 4 ) ( Kim et al, 1998 ; Chae et al, 2012 ; Yang et al, 2017 ), TmDefensin and TmDefensin-like ( TmDef and TmDef-like ) ( Jang et al, 2020b ), TmColeoptericin-A and -B ( TmColeA and − B ) ( Zhu et al, 2014 ; Jang et al, 2020a ), TmAttacin-1a, −1b and -2 ( TmAtt1a , − 1b and − 2 ) ( Jo et al, 2018 ), TmCecropin-2 ( TmCec2 ) ( Ali Mohammadie Kojour et al, 2021 ), and TmThaumatin - like protein-1 and − 2 ( TmTLP1 and − 2 ) ( Noh and Jo, 2016 ; Kim et al, 2017 ), were examined by qRT-PCR with the AMP gene-specific primers ( Table 1 ). A relative quantitative PCR was performed as detailed above in an AMP-specific primer.…”
Section: Methodsmentioning
confidence: 99%